THE EFFECT OF PAIR AND GROUP WORK IN COLLABORATIVE PRE-WRITING DISCUSSION ON STUDENTS’ WRITING QUALITY - Winarti Winarti (Journal of English for Academic and Specific Purposes, 2019)
In foreign language writing classroom, collaborative pre-writing activity is one of common activities used by students to help them generate and evaluate their ideas before they write a text. A teacher usually assigns students to work in pairs or groups to accomplish the activity. However, whether the number of participants in collaborative pre-writing activity influenced the quality of students’ writing or not is still mysterious that need to be investigated further.  This study tried to investigate the effect of the number of participants in collaborative pre-writing discussion on students’ writing quality. 30 participants from non-English department who were studying English as English Specific Purposes were involved in this study. They were required to write an explanation paragraph after being given a certain treatment. The result of the study revealed that the quality of students’ writing was not affected by the number of participants in collaborative pre-writing discussion. Therefore, the implication of the study is teacher can assign students to work collaboratively in pre-writing activity with two or more students. However, some factors need to be considered by teacher such as students learning style, the nature of task, etc.